From marxism to post marxism? - Therborn, Goran (London, 2010)
In this pithy and panoramic work both stimulating for the specialist and accessible to the general reader one of the world’s leading social theorists, Göran Therborn, traces the trajectory of Marxism in the twentieth century and anticipates its legacy for radical thought in the twenty-first.
Keywords: Marxism